Pelatihan Penguasaan Microsoft Office pada Siswa SMAN 2 Tanjung Palas Timur Kabupaten Bulungan - Natalia Susanti, Agnes; Trisyanti, Novriani; Andriyansa, Dede; Yehezkiel; Suwartika Kusumadiarti, Rini; Tisnawati, Rini; Kurniawati, Rina; Seliwati (LPPM Politeknik Piksi Ganesha, 2024)
Microsoft Office mastery training has been conducted at SMAN 2 Tanjung Palas Timur, Bulungan Regency, to enhance students' skills in using Microsoft Office applications. The methods used in this training include delivering materials through brief lectures and self-paced exercises by the students. A significant finding from this training is the marked improvement in students' understanding of Microsoft Office applications. Students also demonstrated increased efficiency and creativity in using these applications for school assignments and extracurricular activities